Nutritional Management and Outcomes in Malnourished Medical Inpatients - Stanga, Zeno; Schuetz, Philipp (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Malnutrition lurks in the background of hospitalized medical patients. A large proportion of patients are malnourished upon hospital admission and patients often experience further nutritional deterioration during their stay and during disease recovery. However, although the negative effects of malnutrition on the outcomes of patients are well recognized, we still struggle to identify appropriate patients and efficacious nutritional interventions to overcome this problem. Recent studies have produced convincing evidence that adequate and timely nutritional management of medical in-patients can contribute to the prevention of negative consequences and thus improve the clinical outcome of patients. This Special Issue of the Journal of Clinical Medicine focuses on multiple practical aspects of nutritional management of medical in-patients, from screening for nutritional risk to the practical implementation of nutritional therapy and its possible complications, including financial aspects, to increasing clinician awareness and knowledge of nutritional care in hospitals.